The XIX International Conference on Electrical Machines - ICEM 2010 2010
DOI: 10.1109/icelmach.2010.5608035
|View full text |Cite
|
Sign up to set email alerts
|

Iso efficiency contour measurement results for variable speed drives

Abstract: The efficiency of variable speed drives with induction motors and permanent magnet synchronous motors has received little attention so far in international standards. However the number of such applications is increasing rapidly and the potential energy savings are large. This paper is based on a measurement campaign of three collaborating research institutes and reports on the efficiency of motors up to 15 kW. The efficiency values are represented by means of iso efficiency contours. From these contours, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Stockman et al [27] demonstrated that the brushless PM motor/VFD has far better efficiency values compared to the IM/VFD.…”
Section: Variable Frequency Drivesmentioning
confidence: 99%
“…Stockman et al [27] demonstrated that the brushless PM motor/VFD has far better efficiency values compared to the IM/VFD.…”
Section: Variable Frequency Drivesmentioning
confidence: 99%
“…Choose this temperature or a temperature slightly lower as test temperature. 6) For a chosen matrix of test points [19], the measurements are performed. Preferably, start with choosing a (nearly) fixed speed and 'scan' the preferred load points starting with the highest torque until the lowest partial load point.…”
Section: Testing Protocolmentioning
confidence: 99%
“…More information on the choice of the test matrix, required density of test points and accuracy linked with such interpolations can be found in [19].…”
Section: Testing Protocolmentioning
confidence: 99%
“…Internationally approved standards or testing procedures of motor/VFD combination are not available at present (Stockman et al, 2010). Since the variable frequency drive can operate the motor over a wide range of speeds, it is important to know efficiency values of VFD/motor combination at each operating point to accurately determine the operating point of a pump, which is known as iso-efficiency contours.…”
Section: Variable Frequency Drivesmentioning
confidence: 99%
“…Since the variable frequency drive can operate the motor over a wide range of speeds, it is important to know efficiency values of VFD/motor combination at each operating point to accurately determine the operating point of a pump, which is known as iso-efficiency contours. Stockman et al (2010) have reported a successful measurement procedures how to…”
Section: Variable Frequency Drivesmentioning
confidence: 99%